1995
DOI: 10.1016/0014-5793(95)01112-r
|View full text |Cite
|
Sign up to set email alerts
|

Insulin stimulates hormone‐sensitive cyclic GMP‐inhibited cyclic nucleotide phosphodiesterase in rat brown adipose cells

Abstract: The presence and regulation of a hormone-sensitive cyclic GMP-inhibited cyclic nucleotide phosphodiesterase (cGl PDE) in rat brown adipose cells was investigated, cDNA clones for two cGl PDE isoforms, cGIPI and cGIP2, have been isolated. Using a rat cGIPI (RcGIPI) cDNA probe, RcGIPI mRN A (~5.3 kb) was detected in Northern blots of both brown and white adipose RNA. cGl PDE was detected in both microsomal and plasma membrane fractions of brown and white adipose cells by Western blotting using anti-RcGIPl peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…PKA phosphorylation of PDE3B is activating, which serves as a negative-feedback loop; interruption of this circuit would be expected to potentiate isoproterenolstimulated glycerol release, as found in our experiments (34,36). Importantly, this provides strong support for the notion that, had activation of PDE3B by Akt been important for antilipolysis, the experimental system would have had the sensitivity to detect this, since the magnitudes of PDE3B activation by Akt and PKA are similar (34,35,50,51). Furthermore, we have shown that no other residue previously identified as a potential target of phosphorylation is important in this process.…”
Section: Discussionsupporting
confidence: 75%
“…PKA phosphorylation of PDE3B is activating, which serves as a negative-feedback loop; interruption of this circuit would be expected to potentiate isoproterenolstimulated glycerol release, as found in our experiments (34,36). Importantly, this provides strong support for the notion that, had activation of PDE3B by Akt been important for antilipolysis, the experimental system would have had the sensitivity to detect this, since the magnitudes of PDE3B activation by Akt and PKA are similar (34,35,50,51). Furthermore, we have shown that no other residue previously identified as a potential target of phosphorylation is important in this process.…”
Section: Discussionsupporting
confidence: 75%
“…The expression of PDE(s) has been poorly investigated in BAT. However, the presence of PDE3 mRNA in this tissue was first demonstrated by in situ hybridisation [22] and the regulation of this isoform is thought to be similar to that in white adipose cells [14]. The data provided in this study confirm that PDE3 is present in BAT but they also show that activity of this isoform represents only half of the total PDE activity, thus suggesting that other PDE(s) play a role in the degradation of cAMP.…”
Section: Discussionsupporting
confidence: 66%
“…10 Tissues were minced and digested at 37°C with the combination of collagenase and DNAse I as described by Omatsu‐Kanbe et al [14]. The floating fractions containing brown adipose cells were washed three times in Krebs Ringer bicarbonate HEPES buffer (120 mM NaCl, 4 mM KH 2 PO 4 , 1 mM MgSO 4 , 1 mM CaCl 2 , 10 mM NaHCO 3 , 30 mM HEPES, pH 7.4) containing 2.5 mM glucose and 200 nM adenosine and then homogenised and processed as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that while PDE3B mRNA levels are generally downregulated in fat tissues, the posttranscriptional regulation of PDE3 activity in brown fat may be different from that of white fat, which must have compensated for the reduced expression of the PDE3B gene. It has been demonstrated that the regulation of PDE3 activity in rat brown adipocytes by insulin and isoproterenol is similar to that in white adipocytes (46). It should be noted, however, that the increased lipolysis that is associated with diabetes can be explained by the reduced PDE3 activity in white adipose tissues, since the brown adipose mass in humans is very small compared with the white adipose mass.…”
Section: Discussionmentioning
confidence: 96%